Analysis Of Determinants Affecting The Volume Of Indonesian Tobacco Exports To Cambodia - Komang Indrayana; Putu Krisna Adwitya Sanjaya (International Journal of Economics, Commerce, and Management, 2025)
Tobacco is one of the leading commodities in the agricultural sector. In the Indonesian agricultural sector, tobacco has been widely exported to various countries. Of the several tobacco export destination countries, Cambodia dominates the Indonesian tobacco export market. Problems related to fluctuations in Indonesia's export volume need serious attention, because this is important to understand the factors that influence the increase and decrease in the volume of Indonesian tobacco exports to Cambodia. Based on the description, the objectives of this study are (1) To analyze the influence of production volume, inflation, and the dollar exchange rate simultaneously on the volume of Indonesian tobacco exports to Cambodia, (2) To analyze the partial influence of production volume, inflation, and the dollar exchange rate on the volume of Indonesian tobacco exports to Cambodia. The data used in this study are secondary data with a total of 32 observations (years), using the multiple linear regression method. This study found that (1) Simultaneously, production volume, inflation, and the dollar exchange rate significantly affect the volume of Indonesian tobacco exports to Cambodia, and (2) Partially, production volume, inflation, and the dollar exchange rate have a positive and significant effect on the volume of Indonesian tobacco exports to Cambodia. Based on the results of the study, it is hoped that the government can pay attention to the causes of fluctuations in the volume of Indonesian tobacco exports.